(3JCKjQ GdVHW GdGLJeGYj Ydi KbGaI GdeQGgbjf(B. "(3fehPL KGfhjI eZOhTI GdQSejI(B"s - (3eGQJjfhS , efis ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3eYgO GdYdhe GdGLJeGYjIs, 2004)
(3JgOa GdOQGSI Edi cTa eOi JCKjQ GdVhGHW GdGLJeGYjI Ydi KbGaI GdeQGgbjf, hGSJHjGf eOi JbHd GdeQGgb dKbGaI eLJeYg heOi GSJHWGfg dgG, hPdc ef NdGd GdJQHjI hGdJfTFI GdGLJeGYjI GdeJeKdJjf HGdCSQI, GdeOQSI, hGdeLJeY, hESJcTGa hage Cge CSGdjH GdVHW GdELJeGYj GdehLhOI OGNdge(B. (3ESJNOeJ GdOQGSI GdefgL GdHfjhj hGSJYGfJ HGdGSJeGQI cCOGI dLeY GdeYdheGJ, hGNJGQJ GdOQGSI YjfI YThGFjI HSjWI eDdaI ef (B160 (3WGdHkG ef GdeQMdI GdKGfhjI aj eOQSI eZOhTI GdQSejI LfhH dHfGf(B. (3CXgQJ GdfJGFL Cf GdeQGgb GSJHWf KbGaI CSQJg hde jYed Ydi JLGhR SdWI hGdOjg, aGfMUQJ GdefGbTI eY GdCe hGfYOeJ eY GdCH hGdCN GdCcHQ(B. (3hGbJUQJ GdJQHjI Ydi GdhYX hGdEQTGO Ohf SeGY GdQCj aj CehQ YOI, aCcKQ ef KdKj GdeQGgbjf jJefhf GdYjT NGQL GdCSQI(B. (3CeG ajeG jNU GdSdWI GdeOQSjI aXgQ Cf GdeOQSI JaQV bSQkG Ydi GdWdGH KbGaI eYjfI(B. (3hHGdfSHI ddeLJeY aEf GdCYQGa hGdJbGdjO hGdYGOGJ JYqO GdqSeI GdCcKQ SjGOI hGdJj jQaVgG GdeQGgb(B. (3hYdi UYjO GdVhGHW GdOjfjI JHjf Cf GdeQGgbjf jJHYhf eHGOF Ojfge HTcd cHjQ eeG jLYd GdCSQI JMGaX Ydi GdQhGHW GdeJjfI(B.s
(3GdfhY (B: (3QSGdIs
Keywords: (3eZOhTIs; Adolescents; Adolescents; Public Sector Secondary Education; Secteur Public Cycle Secondaire; (3GdJYdje GdQSej GdeQMdI GdKGfhjIs; (3GdeQGgbhfs